Gender Representation in English Textbook: A Visual Grammar Analyis - Muzdalifah, Astria; Noorman, Safrina; Gunawan, Wawan (Jurnal Penelitian Pendidikan, 2021)
This study was qualitative descriptive, which investigated what kind of gender features emerged for the male and female represented in image of textbook for elementary school. The data of this study were collected from an English textbook entitled â€œStairway a fun and easy English textbook (for Grade IV of Elementary Schoolsâ€, published by Tiga Serangkai. The data in the present study were in the form of images and texts taken from a textbook. The data were analysed by following the theory of visual grammar by (Kress van Leeuwen, 2006) to analyse the visual text. The study found that there are unequitable gender representations typically because both genders are represented through stereotypical portrayals. Males are represented to dominate language strategies and occupy more public areas, while females are represented to be passive and occupy more private areas. The portrayal of asymmetrical gender representation in the textbook shows that the reflection of the textbook is realized by ideology and inspired by the interest of the society.